Structured deformations and applications. Issue 1 (15th March 2018) - Morandotti, Marco
Abstract: The scope of this contribution is to present an overview of the theory of structured deformations of continua and two applications, all of which involve using this rather new formulation of mechanics problems in contexts that are different from one another, thus showing the power and versatility of the theory. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)